Enhancing the Production Yield of Jatropha and Pongamia Oil-Based Biodiesel by Introducing Nanocatalyst. (16th August 2022) - Nagaraj, Sathiesh Kumar; Ponnusamy, Paranthaman; Gopal, P. M.; Van, Huu Tap; Nguyen, Lan Huong; Kabir, Sadib Bin
Abstract : Fossil fuel depletion, increasing demands of energy, and harmful emission production led to do research on biofuels. In this research, biodiesel is developed by blending of Jatropha and Pongamia oil with the help of magnetic stirrer-assisted transesterification process. Heterogeneous copper-doped titanium oxide catalyst was synthesized by wet impregnation method. The developed catalyst is characterized through XRD and HRTEM analyses and used to enrich the biodiesel yield and fuel properties, viz., viscosity, flashpoint, and fire point. The maximum yield of 90.2% is obtained with catalyst concentration of 3 wt%, reaction time of 3 hrs, temperature of 60°C, and methanol to oil molar ratio of 20 : 1.